Perbandingan Morfologi Sel Darah Pada Apusan Darah Tepi Menggunakan Sari Buah Stroberi (Fragria sp) dan Tomat (Solanum lycopersium) Dengan Metode Wright-Stain - Maulana, Muhammad Nurfajrin; Putri, Nadia Amalia; Pribadi, Qothri Agnia; ‎ ‎, Juleha; ‎, Neni Oktiyani; Cahyono, Jujuk Anton (Jurnal Skala Kesehatan, 2023)
Wright's stain is a stain for blood preparations consisting of methylene blue and eosin reagents. Strawberries contain anthocyanin dyes and tomatoes contain lycopene, both of which have the function of giving a red pigment, making it suitable for use as a substitute for eosin taking into account the acidity of the pH used by eosin solution with alternative dyes to be investigated. The pH of eosin is 5.2 - 6.0 in an acidic environment, while the pH of strawberries is 5.5 - 6.5 and the pH of tomatoes is 6.0-6.5. The purpose of this study was to determine the morphology of blood cells in the peripheral blood smear (SADT) and the effectiveness of natural alternative dyes used. The type of method in this research is Quasi Experiment. The research material used was normal control blood. The data collection technique was in tabular form and analyzed using a descriptive test. The results of microscopic observations of the wright-stain dye as a control with the morphology of erythrocytes, leukocytes, and platelets, produced good staining with a percentage of 96%, while strawberry and tomato juice as alternative colors obtained poor staining results with a percentage of the same amounting to 12.5%. It can be concluded that the natural alternative dyes of strawberries and tomatoes are able to color some blood cells well and have quite good staining quality in some stained blood cells.